Periosteum-Derived Cells as an Alternative to Bone Marrow Cells for Bone Tissue Engineering Around Dental Implants. A Histomorphometric Study in Beagle Dogs - Ribeiro, Fernanda V.; Suaid, Fabricia F.; Ruiz, Karina G. S.; Salmon, Cristiane R.; Paparotto, Telma [UNESP]; Nociti, Francisco H.; Sallum, Enilson A.; Casati, Marcio Z. (Amer Acad Periodontology, 2010)
Background: The aim of this study is to investigate the potential use of periosteum-derived cells (PCs) for tissue engineering in pen-implant defects.Methods: Bone marrow cells (BMCs) and PCs were harvested from seven adult beagle dogs, cultured in vitro, and phenotypically characterized with regard to their osteogenic properties. The animals were then subjected to teeth extraction, and 3 months later, two implant sites were drilled, bone dehiscences created, and dental implants placed. Dehiscences were randomly assigned to one of two groups: PCs (PCs + carrier) and BMCs (BMCs + carrier). After 3 months, the animals were sacrificed and the implants with adjacent hard tissues were processed for undecalcified sections. Bone-to-implant contact, bone fill within the limits of implant threads, and new bone area in a zone lateral to the implant were histometrically obtained.Results: In vitro, phenotypic characterization demonstrated that both cell populations presented osteogenic potential, as identified by the mineral nodule formation and the expression of bone markers. Histometrically, an intergroup analysis showed that both cell-treated defects had similar bone fill within the limits of implant threads and bone-to-implant contact (P>0.05), and although a trend toward higher new bone area values was found for the PC group, there was no significant difference between the experimental groups (P>0.05).Conclusions: Periosteal and bone marrow cells presented a similar potential for bone reconstruction. As such, periosteum may be considered as an alternative source of osteogenic cells in implant dentistry. J Periodontol 2010;81:907-916.
Keywords: Bone marrow; bone regeneration; dental implants; periosteum; tissue engineering